Recurrent pyriform sinus fistula successfully treated by endoscopic Glubran 2 sealing: A rare case and literature review. (1st October 2016) - Di Nardo, Giovanni; Valentini, Valentino; Angeletti, Diletta; Frediani, Simone; Iannella, Giannicola; Cozzi, Denis; Roggini, Mario; Magliulo, Giuseppe
Objectives: The authors present the case of a 3-year-old girl with a history of complicated surgery for removing a third branchial cleft fistula. Methods: An endoscopic approach using N-butyl-2-acrylate and metacrilosisolfolane glue (GLUBRAN 2) to seal the fistula was performed. Results: The clinical and radiological 6-year follow-up confirmed the absence of the fistulous orifice and the persistence of scar due to previous open-neck surgical procedures. Conclusion: endoscopic Glubran 2 sealing has been an effective treatment procedure for branchial fistula.